Improved ROCOF relay for islanding detection of solar distributed generation - J. Rajesh Reddy; A. Pandian (Institute of Advanced Engineering and Science, 2019)
In recent years to meet the energy consumption demand of the world, all are working on renewable distributed generation (RDG) due to shortage of fossil fuels. The RDG systems after integrating with grid, has a disadvantage of islanding in the power system. Islanding is caused, if the RDG is supplying power to load connected due to failures in the grid. As per IEEE 1547 distributed generation (DG) interconnection standards, the islanding should be detected within 2 seconds after islanding. In this paper a hybrid islanding detection scheme is presented with rate of change of frequency (ROCOF) and reactive power injection with positive feedback. It will reduce the non detection zone (NDZ) of passive ROCOF relay to zero and can detect balanced islanding. The computer simulations are performed on MATLAB-2016. The simulations results show the effective performance of the proposed method.